Dose and Duration of Oxytocin to Prevent Postpartum Hemorrhage: A Review - Roach, Michelle K.; Abramovici, Adi; Tita, Alan T.N. (American Journal of Perinatology, 2013)
Objective Oxytocin, the most commonly used uterotonic agent in the United States to prevent postpartum hemorrhage, has no established standard dose. The aim of this review is to present data on oxytocin dosing for the prevention of postpartum hemorrhage.Study Design We conducted a PubMed search for clinical trials that utilized oxytocin for hemorrhage prophylaxis following either vaginal or cesarean delivery. We further narrowed the results to studies that compared alternative dosing and duration of oxytocin administration.Results Seven of 46 eligible reports were selected for detailed review. We compared the dose and duration of oxytocin used, study population, and outcomes (estimated blood loss, need for additional uterotonics, and change in hematocrit after delivery). Dose of oxytocin used ranged from 5 to 100 IU and duration of administration ranged from 5 to 30 seconds (intravenous bolus) to 8 hours diluted in crystalloid.Conclusion Overall, higher infusion doses (up to 80 IU/500 mL) and bolus doses of oxytocin appear to be more effective than lower doses or protracted administration of a fixed dose at reducing outcome measures of postpartum hemorrhage, particularly among cesarean deliveries.
Keywords: oxytocin; dose; postpartum; hemorrhage